Pengaruh Kadar Air Awal Dan Surcharge Pressure Pada Uji Karakteristik Pengembangan Tanah Ekspansif - Diana, Wilis; Hartono, Edi; Widianti, Anita (MEDIA KOMUNIKASI TEKNIK SIPIL, 2017)
Expansive soils experience volumetric changes due to water content changes. These volumetric changes cause swell and shrink movement in soils, which in turn will inflict severe damage to structures built above them. A Proper understanding of how the expansive soil behaves during the wetting/drying process is essential for assessing the mitigation action of expansive soil hazard and design suitable foundation. The structures that build above expansive soil bed are susceptible to heave and to withstand swell pressure, thus the swell pressure must be considered in the design. This study focuses on swelling properties of two expansive clay from Ngawi, East Java and Wates, Yogyakarta. Laboratory test on disturbed samples is used to identified and to measured swelling properties. A series of swelling test was performed under constant soil dry density. The influence of initial water content and surcharge pressure on swelling properties (i.e swell percent and swell pressure) of compacted samples were investigated. The swelling properties test used ASTM standard 4546-03 method B. It was found that the lower initial water content the higher the swell percent, but the swell pressure seems not to be affected by initial water content. At the same initial water content, swell percent decrease with the increase of surcharge pressure, but swell pressure remains unchanged.